2000
DOI: 10.3928/1542-8877-20001101-05
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sealing Sclerotomies for Sutureless Pars Plana Vitrectomy

Abstract: * OBJECTIVE: To determine the efficacy of self-sealing pars plana sclerotomies for vitrectomy and to identify complications associated with this new technique. * METHOD: There were 150 self-sealing sclerotomies performed in 50 patients undergoing pars plana vitrectomy between October 1996 and March 1998. * RESULTS: Of the 150 sclerotomies, 115 (76.6%) did not require suturing while 35 (23.3%) were closed with one radial 7.0 vicryl suture. The scleral tunnel incisions ensured minimal loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Minimally invasive vitreoretinal surgery has been proposed in the past by other authors. 5 – 8 , 10 , 25 Chen 1 proposed a sutureless tunnel-based sclerotomy, but the case series reported in that study revealed difficulty in the passage of conventional instruments along with several complications, including wound extension, dehiscence, and leakage, vitreous and/or retinal incarceration, hemorrhage, retinal tears, and dialysis. 1 , 5 , 8 As a result of the weakness and reduced efficiency of the 27-G instruments, some studies have reported the necessity of converting to a larger-gauge system.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive vitreoretinal surgery has been proposed in the past by other authors. 5 – 8 , 10 , 25 Chen 1 proposed a sutureless tunnel-based sclerotomy, but the case series reported in that study revealed difficulty in the passage of conventional instruments along with several complications, including wound extension, dehiscence, and leakage, vitreous and/or retinal incarceration, hemorrhage, retinal tears, and dialysis. 1 , 5 , 8 As a result of the weakness and reduced efficiency of the 27-G instruments, some studies have reported the necessity of converting to a larger-gauge system.…”
Section: Discussionmentioning
confidence: 99%
“…Sutureless 25-gauge pars plana vitrectomy has the potential to reduce the length of surgery and postoperative inflammation at the sclerotomy sites, thus decreasing patient discomfort postoperatively and hastening recovery (Chen 1996;Kwok et al 1999;Jackson 2000;Lam et al 2000;Rahman et al 2000;Fujii et al 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…This method aimed to avoid suture-related complications, and to shorten the operation time. However, related to the technique, surgical difficulties and several complications such as wound leakage, dehiscence and hemorrhage, retinal break, vitreous and/or retinal incarceration, and dialyses have been reported (4,5). Furthermore, the scleral tunnel technique requires conjunctival dissection and subsequent suturing (5,6).…”
Section: Introductionmentioning
confidence: 99%